Innovation, tort law, and competition - Florian Baumann; Klaus Heine (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
In this paper, we examine the link between innovative activity on the part of firms, the competitive pressure to introduce innovations and optimal damages awards. While innovative activity brings forth valuable new products for consumers, competitive pressure in the ensuing innovation race induces firms to launch innovations too early, thereby raising the likelihood of severe product risks above the optimal failure rate. Introducing innovations too early may call for the application of punitive damages instead of mere compensation of harm caused, in order to decelerate such welfare-reducing innovation races. The optimal tort system is accordingly highly dependent not only on the expected profits and the effectiveness of time delays with respect to reducing expected harm, but also on the competitive environment in which firms operate.
Keywords: K13; L13; O31; 330; competition; innovation; punitive damages; tort law